If AB does not equal 3x then AB 3x or AB 3x?
I think you mean (3x ± 1)^2 = (3x+1)(3x-1)?
2x minus 3x is equal to -x.
-3x + 10x = 7x 3x + 3x = 6x
Two chords and are equidistant from the center of a circle AB equals 3x plus 7 and CD equals 27 x Solve for x?
Chords equidistant from the center of a circle have equal length, so 3x + 7 = 27x Subtract 3x from each side: 7 = 24x Divide each side by 24: x = 7/24
X= -2 ! Since the equation must equal zero - 17+3x must equal 11. The variable 3x HAS to equal -6... therefore x is equal to minus 2.
ab=1a+1b a is equal to either 0 or two, and b is equal to a
2x + 20 = 3x 20 = 3X - 2X 20 = X
No. 3x plus 2x = 5x. 3x multiplied by 2x = 6x²
plot 4y then 3x
If this is algebra then; 3x plus 12x = 15x
eq: 3x+5=7 =3x=7-5 =3x=2 =x=2/3
Expressed algebraically, 3x times 4 is equal to 12x.
4x + 5 = 3x + 8 4x-3x + 5 - 5 = 3x - 3x + 8 -5 x = 3
3x+3=0 -3 = -3 = 3x=-3 /3 /3 x= -1
3x = 7-5x 8x=7 x = 7/8 x = 0.875
y = -1x/2 3x + 6y = 0 -3x -3x __________ 6y = 0 - 3x --- -------- 6 6 y= -3x/6 y= -1x/2
If you mean: 3x-(2x+4x-6) then 3x-2x-4x+6 simplifies to 6-3x
y = 12. It's the transitive property. y = 12 = 3x.
well what does it equal to find out
wat does 2y-3x-6 equal
4(3x+7) = 12x + 28
If: 3x-4 = or > 11 Then: 3x = or > 15 So: x = or > 5
If 3x - 9 = -6 then 3x must equal 3. Therefore x = 1 !
By subtracting 2x from 3x and getting x, which is equal to 35.
y = 15 (by transitivity)
They are two regions of the Cartesian plane with the straight line 3x + 4y = 12 defining their boundary. That line is not part of either region.
3x - 3x -1 + 2x -1 = 0 0 - 1 + 2x - 1 = 0 2x - 2 = 0 2x = 2 x = 1
You need to provide more information in order to answer this question. However, you need to use either Subsitution or Elimination. Substitue the equation of Line AB into the equation of Line CD. E.g. Line AB y=2x Line CD y=3x+2 2x=3x+2 3x-2x=-2 x=-2 Sub x=-2 into either equation y=2(-2) y=-4 Therefore, the point of intersection is (-2, -4).
3x=18 x=18/3 x=6
You can't solve 5x+3x there isn't a equal sign. But you can simplify it to be 8x
In the equation 3x plus 7 equals 13, x is equal to 2.
We do not know if 3x - 1 is prime because we do not know what x is equal to here.
Point c is between the endpoints of segment ab if ac equals 2x minus 1 cb equals 3x and ab equals 9 solve for x and find ac and cb?
ac + cb = ab = 9 2x - 1 + 3x = 9 5x -1 = 9 So 5x = 10 Thereby x =2. Also ac = 3 and cb = 6
3x plus -5 equal 7. so x is 4 so 3times 4 is 12-5 will equal 7.
19 (7 + 12 = 4x - 3x)
I assume there is an equal sign somewhere. 3x-y = 6?? slope =3
If: 8-1/3x = 16 Then: x = -1/24
3x = x+8 so 3x-x = 8 hence 2x = 8 and so x = 4
If 3x equals 72 then you would have to take 3x divided by three and 72 divided by 3 because you have to do it to the same side. So if 3x=72 then x would equal 24.
It depends. Do you mean 3X as in 3 times X or do you mean 3 subtracted from X? (By the way, roman numerals are always capitalized) If you mean the former, then 3X is 30 which is equal to XXL (L being 50 and XX being the 20 subtracted from it). If you mean the latter, the 3X = 7 which is not equal to XXL or 30.
This type of statement is called a difference of squares. If you see an equation in the form: a2 - b2 then it is also equal to: (a + b)(a - b) In this case 9x2, and 25 are both perfect squares. 9x2 is equal to (3x)2 and 25 is equal to 52, so the that statement can be factored out as: (3x - 5)(3x + 5)
What are the values of the variables when the equal terms of 3x plus 5y plus 7z have a sum of 357 showing work?
If 3x, 5y and 7z are equal terms, them each of them will equal one third of 357, or 119. 3x = 119 x = 39 and 2/3 5y = 119 y = 23 and 4/5 7z = 119 z = 17
3x+2y-7=0 2y=-3x+7 y=1/2(-3x+7) or -3/2 x +7/2
10 -3x+8x = 25 -3x+8x = 25-10 5x = 15 x = 3
what does the equation equal? if it equals zero: 0= 3x(4-11) 0=3x(-7) 0=3x 0=x if the equation doesn't equal anything, it means it's just an expression meaning you can't solve for x, you can only reduce (and this equation is already reduced). if the equation equals y, you need another equation and use either substitution or elimination to solve for x.
2y = -3x - 10 ∴ y = -3x/2 - 5 Let Y equal zero, then: 0 = -3x/2 - 5 ∴ 3x/2 = -5 ∴ 3x = -10 ∴ x = -10/3 So the y-intercept occurs at the point (-10/3, 0)
If you mean: (3x-1)(x+1) = 0, then it is 3x squared+2x-1 = 0. Its solutions are: x = 1/3 or x = -1.
It depends on what the answer is
It is equal to 21x You can not find x.
This is a difference of two squares (DOTS) question on factorisation. 9x2 - 100 = (3x)2 - (10) = (3x - 10)*(3x + 10)